Structural Evaluation and Antibacterial Sensitivity of Iron (III) Complexes of 4-n-hexyloxybenzoylhydrazine with Some Aliphatic and Aromatic - Islam, M. Al-Amin-Al-Azadul; Mumit, M. A.; Pal, T. K.; Alam, M. A. (Journal of Scientific Research, 2012)
The condensation reaction of N-alkylidene or N-arylidene-(4-n-hexyloxy)benzoylhydrazone [L] (1-7) where, R= formaldehyde (1), acetaldehyde (2), butyraldehyde (3), cinnamaldehyde (4), 4-N,N-dimethylaminobenzaldehyde (5), 2-hydroxybenzaldehyde (6) and 4-methoxybenzaldehyde (7) with Fe(III) chloride hexahydrate afforded octahedral (8-9) [Fe(L3).nH2O] and square-pyramidal (10-14) [Fe(L2)Cl.nH2O] complexes. The complexes (8-10) were obtained in presence of pyridine and the complexes (11-14) were obtained by the direct reaction of the Schiffs bases with Fe3+ ion. The complexes were characterized by magnetic moment measurement, UV-visible, infrared, 1H-NMR and TGA (Thermo gravimetric analysis) studies. The Schiffs bases containing small alkyl group at the hydrazine moiety formed octahedral complexes, while the bulky/aryl/substituted aryl moiety, yielded five coordinated square-pyramidal complexes. The complexes were found to be quite stable and decomposition of the complexes ended with ferric oxide as final product. Complexes (10) and (13) showed no activity against all the bacteria. Complexes (8), (9) and (12) showed resistance while the complex (14) manifested intermediate antibacterial activity. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.9807 J. Sci. Res. 4 (3), 635-64 (2012)